CO2 refrigeration system heat recovery and thermal storage modelling for space heating provision in supermarkets: An integrated approach. (15th April 2020) - Maouris, Georgios; Sarabia Escriva, Emilio Jose; Acha, Salvador; Shah, Nilay; Markides, Christos N.
Highlights: A model for heat recovery via refrigeration with thermal storage is presented. Model informs decision-makers of the potential the solution has in supermarkets. Fossil fuel use can be displaced with a small increase in electricity costs (2–3%). Annual energy demand reduction of 17–18% is feasible with such systems. Thermal storage increases the potential of heat recovery by 11–12%. Abstract: The large amount of recoverable heat from CO2 refrigeration systems has led UK food retailers to examine the prospect of using refrigeration integrated heating and cooling systems to provide both the space heating and cooling to food cabinets in supermarkets. This study assesses the performance of a refrigeration integrated heating and cooling system installation with thermal storage in a UK supermarket. This is achieved by developing a thermal storage model and integrating it into a pre-existing CO2 booster refrigeration model. Five scenarios involving different configurations and operation strategies are assessed to understand the techo-economic implications. The results indicate that the integrated heating and cooling system with thermal storage has the potential to reduce energy consumption by 17–18% and GHG emissions by 12–13% compared to conventional systems using a gas boiler for space heating. These reductions are achieved despite a marginal increase of 2–3% in annual operating costs. The maximum amount of heat that can be stored and utilised is constrained by the refrigeration system compressor capacity. These findings suggest that refrigeration integrated heating and cooling systems with thermal storage are a viable heating and cooling strategy that can significantly reduce the environmental footprint of supermarket space heating provision and under the adequate circumstances can forsake the use of conventional fossil-fuel (natural gas) boiler systems in food-retail buildings.